Driving Mode Control of A Multilayered Thin Electrostatic Actuator Supported By Lubricating Oil For Ultra-Precision Positioning - Md Ghazaly , Mariam (2012)

(untitled)
Fine stages are widely used in microscope systems, optical systems, and manufacturing systems. Electrostatic actuators have some advantages in terms of their low heat production and material availability. They are also able to transmit power without mechanical contact and do not require hinges. In addition, the multilayered structure can increase the produced thrust force.